2020
DOI: 10.1051/0004-6361/202039204
|View full text |Cite
|
Sign up to set email alerts
|

Dense cores in the Seahorse infrared dark cloud: physical properties from modified blackbody fits to the far-infrared–submillimetre spectral energy distributions

Abstract: Context. Infrared dark clouds (IRDCs) can be the birth sites of high-mass stars, and hence determining the physical properties of dense cores in IRDCs is useful to constrain the initial conditions and theoretical models of high-mass star formation. Aims. We aim to determine the physical properties of dense cores in the filamentary Seahorse IRDC G304.74+01.32. Methods. We used data from the Wide-field Infrared Survey Explorer (WISE), Infrared Astronomical Satellite (IRAS), and Herschel in conjuction with our pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 97 publications
(152 reference statements)
0
3
0
Order By: Relevance
“…The clumps appear dark at 70 µm and lie above the mass-radius threshold for highmass star formation proposed by Baldeschi et al [58], as shown in Figure 7 of a study by Miettinen et al [21], and which is given by M thresh = 1 732 M ⊙ × (R/pc) 1.42 when scaled to our assumptions about the dust opacity and gas-to-dust mass ratio [45]. However, the present data do not suggest the clumps to be candidates for being high-mass prestellar clumps, but only high-mass starless clumps.…”
Section: Dynamical State Of the Clumpssupporting
confidence: 57%
See 1 more Smart Citation
“…The clumps appear dark at 70 µm and lie above the mass-radius threshold for highmass star formation proposed by Baldeschi et al [58], as shown in Figure 7 of a study by Miettinen et al [21], and which is given by M thresh = 1 732 M ⊙ × (R/pc) 1.42 when scaled to our assumptions about the dust opacity and gas-to-dust mass ratio [45]. However, the present data do not suggest the clumps to be candidates for being high-mass prestellar clumps, but only high-mass starless clumps.…”
Section: Dynamical State Of the Clumpssupporting
confidence: 57%
“…It was again assumed that the gas temperature is equal to the dust temperature. The clumps were assumed to have a radial density profile of the form n(r) ∝ r −1.6 , which is consistent with those derived for Galactic high-mass star-forming clumps (see [45] and references therein). The powerlaw index of the density profile, p, modifies the virial mass as M vir ∝ a −1 , where a = (1 − p/3)/(1 − 2p/5) (see [46] and references therein).…”
Section: Virial Analysis Of the Cloud And Its Clumpsmentioning
confidence: 90%
“…The thresholds were scaled to the assumptions we adopted here (see Eqs. ( 9) and (10) in Miettinen (2020)). The G1.75-0.08 clumps lie above the thresholds, for example by factors of 1.9 ± 0.3 (clump A) and 1.6 ±0.3 (clump B) above the Baldeschi et al (2017) limit.…”
Section: Physical Properties Of the Clumps And Their Potential For Hi...mentioning
confidence: 93%
“…The mid-IR or far-IR to submillimetre SEDs of the clumps in G1.75-0.08 and G11.36+0.80 were fitted by a modified blackbody (MBB) function using the method and assumptions of Miettinen (2020;Sect. 3.1 therein).…”
Section: Sed Analysismentioning
confidence: 99%
See 1 more Smart Citation